OBSERVATIONS ON THE INDIAN MACKEREL, RASTRELLIGER CANAGURTA (CUV) FROM PURSE-SEINE CATCHES ALONG GOA COAST - Doiphode, P V (Indian Journal of Fisheries, 2011)
The present study is based on 351 specimens of the Indian mackerel(Rastrelliger kanagurta) collected during the period October, 1965 to January,1966 from the purse-seine catches at Panaji. No appreciable difference betweenmales and females has been noticed in the length-weight relationship of mackerelobserved in present investigation. The predominant group in the food item wasDinophyceae constituting about 50.3% in count value. The other importantgroups were Diatoms, Copepods, Bivalves and Miscellaneous items.